PERLINDUNGAN HUKUM TERHADAP KONSUMEN JASA ASURANSI DI INDONESIA - Deny Guntara; Anwar Hidayat; Irma Garwan (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2017)
ABSTRACT Various legal instruments made to provide protection to consumers, especially consumers of insurance services, include the establishment of BMAI (the Indonesian Insurance Mediation and Arbitration Agency), OJK (Financial Services Authority), as well as those accommodated in the Consumer Protection Law which includes BPKN (National Consumer Protection Agency), LPKS (Non-Government Consumer Protection Institution, and BPSK (Consumer Dispute Settlement Agency), are layered instruments that consumers can use to fortify themselves from fraudulent acts and arbitrarily even ignore consumer rights committed by business actors. However, whether these devices are sufficient enough, in connection with the many complaints from the public against business actors, especially insurance service businesses. Many things affect the phenomenon of society, especially consumers of insurance services who feel that they are still not protected by the layers of legal instruments made, including factors from the consumers themselves, factors of business actors, law enforcement factors, and other supporting factors it should run in an ideal and harmonious manner. Keywords : Consumer Insurance Services, Insurance Business Actors, Consumer Protection